2014 HUNCH SPIDER - Woods, Jonathon (Proceedings of the Wisconsin Space Conference, 2015)
HUNCH is an instructional partnership between NASA and high school, intermediate school, and middle school students. This partnership benefits both NASA and students. NASA receives cost-effective hardware, while students receive real-world hands-on experiences. The results of this cooperation is the inspiration for the next generation of researchers and space explorers. Our team was comprised of seven members: Eli Rand, Nicholas Nolting, Jonathon Woods, Luke Goetsch, Paul D'Amico, Joey Dominski, and Daniel Barr. Each member of our team had designated roles within the group, but we all worked together to advance towards goals and meet deadlines.